Can a 2-week block of high intensity interval endurance training boost regeneration? - Bubeck, D.; Gerdes-Roeben, H.; Alt, W. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
It is well known that endurance training realised in long slow distance mode has a positive effect on the regenerative capacity. Additionally it can be seen that high intensity interval training is very useful to enhance the capability in endurance, especially when it is organized in a block training structure. This leads to the question of this study: Has a 2-week block of high intensity endurance training an influence on the vegetative nervous system and enhances therefore the ability to regenerate better? In order to analyse this, a trained athlete (24years, male) performed a two-week high intensity interval program (HIT) with 14 training sessions. Before and after this HIT block one normal week without any additional training programs was analysed. Training program consisted of a 4x4x3 scheme at an intensity level of 90% of VO2max executed on a cycle ergometer. In order to get information`s about the effect on the regenerative system (vegetative nerve system - n. parasympathicus) heart rate variability (HRV) was measured during every night with a 12 hours EKG analysis (Schiller Medilog AR4/AR12). The training and the total daily amount of load was measured by analysing the heart rate 12 hours a day using a Polar electro heart rate monitor and a Polar actigraph for the daily load in MET`s. In order to look at the training effect on the vegetative nervous system the EKG was frequency analysed and the frequencies were allocated to the bandwidths committed by the Task Force of the European Society of Cardiologyand the North American Society of Pacing and Elektrophysiology in 1996. The results show that the impact of the training stimulus can be seen as slightly higher values of the heart rate or the MET`s during the both high intensity training weeks. But both values were reduced in the week after the training intervention. The training stimulus leaded to clear reductions of the heart rate at day and in the night in week four. Analysing the parasympathetic dominated high frequency values of the heart rate variability it can be seen that the values were reduced during the high intensive training phase. After finishing the training process a clear rise in the high frequency values can be seen. Analysing the log of the high frequency/low frequency values of the heart rate shows the same. Additionally using the HRV to predict phases of deep sleeping shows that after the two training weeks the athlete has clear longer deep sleeping phases. These results show that a high intensity training in block training organisation can enhance the ability to regenerate analysed by the higher activity of the nervous parasympathicus.